2006
DOI: 10.1002/pd.1422
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive genotyping of 9 Y‐chromosome specific STR loci using circulatory fetal DNA in maternal plasma by multiplex PCR

Abstract: This assay provides a sensitive, accurate and efficient method for noninvasive prenatal genetic diagnosis and forensic casework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…[1][2][3][4] Prenatal genetic diagnosis using maternal plasma or serum has been developed recently. 5,6 However, when these techniques are applied to blood samples, it must be considered that PCR inhibitors in the specimens may lead to possible false-negative or reduced sensitivity despite advanced DNA purification methods. For example, even after DNA purification steps are used before PCR, a 14% false-negative rate has been observed for hepatitis B virus detection, most probably due to incomplete removal of PCR inhibitors.…”
mentioning
confidence: 99%
“…[1][2][3][4] Prenatal genetic diagnosis using maternal plasma or serum has been developed recently. 5,6 However, when these techniques are applied to blood samples, it must be considered that PCR inhibitors in the specimens may lead to possible false-negative or reduced sensitivity despite advanced DNA purification methods. For example, even after DNA purification steps are used before PCR, a 14% false-negative rate has been observed for hepatitis B virus detection, most probably due to incomplete removal of PCR inhibitors.…”
mentioning
confidence: 99%
“…Scheffer et al combined both PCR results for the Y-linked sequences, SRY and DYS14, for fetal gender determination and concluded that the DYS14 assay targeted a multi-copy sequence and therefore had a higher sensitivity than SRY (30). Deng et al sought nine Y-STR loci of fetal DNA in maternal blood and found that the numbers of Y-STR loci, where the maximum allelic size was less than 100, 137 and 180 bp, observed in Chinese individuals, were one, five, and nine loci, respectively (31). The present study applied the conventional PCR method specialized for amplifying polymorphic X and Y miniSTRs, and utilized an algorithmic based genotyping approach to find fragmented fetal DNA in maternal plasma with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Because foetal cfDNA sequences are fragmented and generally present in sizes of <150 bp (with few longer than 250 bp) [17], it is difficult to obtain sufficient effective loci using a commercial STR typing kit, especially for a female foetus [9,10]. Although mini-STR analysis has been implemented as an alternative [11], SNP analysis provides a greater guarantee of genotyping fragmented DNA because the variations of interest are much shorter.…”
Section: Introductionmentioning
confidence: 99%
“…In forensic science, recent research has sought to develop a universal approach to non-invasive paternity analysis by genotyping the paternally inherited alleles in the maternal plasma DNA using STR and single-nucleotide polymorphism (SNP) markers [9][10][11][12][13][14][15][16]. Because foetal cfDNA sequences are fragmented and generally present in sizes of <150 bp (with few longer than 250 bp) [17], it is difficult to obtain sufficient effective loci using a commercial STR typing kit, especially for a female foetus [9,10].…”
Section: Introductionmentioning
confidence: 99%